Upaya Peningkatan Aktualisasi Diri Pada Klien Dengan Harga Diri Rendah Di Rsjd Arif Zainudin Surakarta - Reynaldi, Garry, Arif Widodo, A.Kep., M.Kes (2016)
Schizophrenia is a group of clinical syndrome characterized by cognitive changes , emotions, perceptions and other aspects of behavior. Background : The concept itself is a picture of self-concept as an idea , a feeling and onfidence to know and are ready to connect and communicate with others , low self esteem is feeling worthless, mean and low self-esteem due to a negative evaluation of self and ability self. Clients with low self-esteem in RSJD dr . Arif Zainudin Surakarta in 2014 as many as 620 patients in January and 647 patients in February. 2 Objective : Authors can understand nursing care in patients with a diagnosis of low self esteem dibangsal Sena RSJD dr . Arif Zainudin Surakarta. Methods : The method used is descriptive case study approach , is to perform nursing care at lower self pasienharga ranging from assessment , intervention , implementation and evaluation of nursing. Results : After 3x24 -hour nursing care for patients with low self esteem issue is resolved in part and interventions should be continued. Conclusion : The issue is resolved partially , thus requiring more care in and cooperation with other medical teams , clients and families that are indispensable for the success of nursing care . The influence of herapeutic communication therapy to increase its positive capabilities clients before and after the intervention . Recommended for clients low self-esteem as an act of self- nursing .